MOTIVATIONAL ANALYSIS OF ORGANISATIONAL CLIMATE ON EMPLOYEE SATISFACTION - A. Palani; P. Kumarasamy (International Journal of Psychosocial Rehabilitation, 2020)
Organisational environment is very critical because it very much affects workplace productivity. Similarly, the efficiency of labour that can be measured by the organisation’s environment or community in which the employee works. With a pleasant organisational climate, a conducive working atmosphere will be created which will manifest among all employees in harmonious and harmonious working relations. Based on the description discussed above, it can be concluded that the organisational climate has an effect on employee motivation. Employees are more motivated by their own desires. Individuals can act solely out of curiosity and the desire to learn without expecting rewards or in other words doing work just to satisfy the sense of satisfaction arising out of curiosity, self-expression, and self-challenge.